PENGARUH KUALITAS JASA DAN PENANGANAN KOMPLAIN TERHADAP KEPUASAN PELANGGAN PERUSAHAAN FUMIGASI PADA CV. ARMANDA NUSANTARA - Rachmawati, Yuni; Tjahjono, Endro; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2018)
Each fumigation company has its own advantages in running company both in terms of service quality, complaint handling, price and others in order to improve customer satisfaction. This study aims to determine the effect of service quality and complaint handling on customer satisfaction in CV. Armanda Nusantara. CV. Armanda Nusantara is one of the fumigation companies in Surabaya that has many customers and exist in the world of fumigation.Number of customer as population in this research is 135 subscribers, and the sample specified in this research as 101 Sampling  using  a sampling  method saturated. Data collection technique was obtained by spreading the questionnaire through online media or email sent to the customers CV. Armanda Nusantara. then the results of data collection were analyzed using multiple regression analysis.From the analysis result obtained:1. There is individual influence of service quality to customer satisfaction and complaint handling to customer satisfaction proven and accepted reality of partial test result (t) obtained with level of significance <0,05.2. There is mutual influence of service quality and complaint handling to customer satisfaction proven and accepted reality of partial test result (F) obtained with level of significance <0,000.3. Variable of service quality and handling of complaint have strong relation to customer satisfaction equal to 75,9% and beside that independent variable have contribution equal to 76,4% dependent variable and the rest 23,6% influenced by other variable.  Keyword : Service quality, Complaint handling, dan Customer satisfaction